Budget and revenue allocation to states/local governments 2002 - Nigeria. Federal Ministry of Finance (Abuja: Federal Ministry of Finance, 2002)
This work is the summary of revenue allocated to states and local government areas in Nigeria in 2002.
oif 03/10/2019
Nigeriana
Keywords: Budgets; Expenditure, Public; Revenue allocation; Nigeria